Robust economic design of NP-chart under different process and economic parameters scenarios. Issue 1 (2nd January 2023) - Attia, Ahmed M.; Abdel-Aal, Mohammad A. M.
ABSTRACT: Control charts are one of the most commonly used statistical process control (SPC) tools in industry or service sectors to improve quality and productivity. The control chart design of a particular process is a well-established and vibrant area of research. It considers the techniques that allow decision-makers to decide on the optimal values of the design parameters. However, these design techniques are not reliable in a dynamic production environment. In such cases, the Robust Economic Control Chart Design (RECCD) approach is more reliable because it considers all possible scenarios of model parameters. This paper aims to develop a RECCD model for np-chart design to mitigate the risks associated with the uncertainty in the economic and process parameters of the production environment. A case study from an automotive manufacturer is used, and sensitivity analysis is carried out to show the effectiveness of the RECCD technique for the np-chart design. It has been shown that the proposed approach can achieve a 45.56% reduction in the total cost compared to the traditional design.